2015
DOI: 10.1590/1519-6984.15513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of injuries caused by anthropic action in snakes from Brazil

Abstract: Human behavior toward wild animals is defined by cultural influences and often is affected by lack of knowledge, mainly in situations of confrontation. The present study was conducted between 2008 and 2013, involving analysis of snakes that had suffered injuries belonging to the reptile collections of Centro Universitário de Lavras and Universidade Federal de Juiz de Fora. The injuries were classified according to location on the body. Among the 449 specimens analyzed, 245 specimens showed injury to some part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
2
5
0
2
Order By: Relevance
“…Men described mostly positive behaviors in response to interaction with amphibians and reptiles, tending to have few neutral behaviors in both groups. This indicates that, although snakes are perceived as dangerous animals, this usually does not lead to defensive behavior that implies the threat of species in the study region, a phenomenon previously reported in other parts of Latin America [2,45,71,73] where the conservation status of different species is put at risk by the effect of the controlling hunt and the use of this group of animals with magical-religious purposes. In contrast, women in the surveyed population tend to have more negative behaviors in the interaction with amphibians compared to reptiles.…”
Section: Interactionsupporting
confidence: 57%
See 1 more Smart Citation
“…Men described mostly positive behaviors in response to interaction with amphibians and reptiles, tending to have few neutral behaviors in both groups. This indicates that, although snakes are perceived as dangerous animals, this usually does not lead to defensive behavior that implies the threat of species in the study region, a phenomenon previously reported in other parts of Latin America [2,45,71,73] where the conservation status of different species is put at risk by the effect of the controlling hunt and the use of this group of animals with magical-religious purposes. In contrast, women in the surveyed population tend to have more negative behaviors in the interaction with amphibians compared to reptiles.…”
Section: Interactionsupporting
confidence: 57%
“…However, this may be due to the difference in the classification of positive and neutral reactions, where the behavior of standing still or moving away is considered neutral for the interaction with amphibians, whereas it is positive for the interaction with reptiles. The above is based on the idea that possible positive behaviors towards reptiles (specifically snakes) do not consider transporting the animal to a safe place, due to its potential danger [71][72][73].…”
Section: Interactionmentioning
confidence: 99%
“…Men described mostly positive behaviors in response to interaction with amphibians and reptiles, tending to have few neutral behaviors in both groups. This indicates that, although snakes are perceived as dangerous animals, this usually does not lead to defensive behavior that implies the threat of species in the study region, a phenomenon previously reported in other parts of Latin America [72,74]. In contrast, women in the surveyed population tend to have more negative behaviors in the interaction with amphibians with respect to reptiles.…”
Section: Discussionsupporting
confidence: 54%
“…However, this may be due to the difference in the classification of positive and neutral reactions, where the behavior of standing still or moving away is considered neutral for interaction with amphibians, whereas it is positive for interaction with reptiles. The above is based on the idea that possible positive behaviors towards reptiles (specifically snakes) do not consider transporting the animal to a safe place, due to its potential danger [7274].…”
Section: Discussionmentioning
confidence: 99%
“…As serpentes peçonhentas encontradas em território brasileiro, estão atualmente agrupadas em 6 gêneros: Bothrops, Lachesis, Botriopsis, Porthidium, Bothrocophias e Crotalus (Família Viperidae) e Micrurus (Família Elapidae) (Ávila et al, 2013;Fenker et al, 2014;Lomonte et al, 2016;Machado et al, 2020). No estado de Goiás foram registradas a ocorrência dos gêneros Bothropos (jararacas), Crotalus (cascavel) e Micrurus (corais verdadeiros), não havendo registro para Lachesis, Porthidium e Botriopsis, sendo estes dois últimos gêneros uma divisão do gênero Bothrops (Fenwick et al, 2009;Gouveia, et al, 2015).…”
Section: Introductionunclassified